Interdomain flexibility of Chikungunya virus nsP2 helicase-protease differentially influences viral RNA replication and infectivity - Law, Yee-Song (2022)
Chikungunya virus (CHIKV) is a mosquito-borne alphavirus responsible for chikungunya fever. Nonstructural protein 2 (nsP2), a multifunctional protein essential for viral replication, has an N-terminal helicase region (nsP2h), which has both nucleotide triphosphatase and RNA triphosphatase activities, as well as a C-terminal cysteine protease region (nsP2p), which is responsible for nonstructural polyprotein processing. The two functional units are connected through a linker of 14 residues. Although crystal structures of the helicase and protease regions of CHIKV nsP2 have been solved separately, the conformational arrangement of the full-length nsP2 and the biological role of the linker remain elusive. Using the small-angle X-ray scattering (SAXS) method, we demonstrated that the full-length nsP2 is elongated and partially folded in solution. The reconstructed model of the structure of nsP2 contains a flexible interdomain linker, and there is no direct interaction between the two structured regions. To examine the function of the interdomain linker, we constructed and characterized a set of CHIKV mutants. The deletion of three or five amino acid residues in the linker region resulted in a modest defect in viral RNA replication and transcription but completely abolished viral infectivity. In contrast, increasing the flexibility of nsP2 by lengthening the interdomain linker increased both genomic RNA replication and viral infectivity. The enzymatic activities of the corresponding mutant proteins were largely unaffected. This work suggests that increasing the interdomain flexibility of nsP2 could facilitate the assembly of the replication complex (RC) with increased efficiency and promote virus production.IMPORTANCE CHIKV nsP2 plays multiple roles in viral RNA replication and virus-host interactions. The helicase and protease regions of nsP2 are connected through a short linker. Here, we determined that the conformation of full-length CHIKV nsP2 is elongated and that the protein is flexible in solution. We also highlight the importance of the flexibility of the interdomain of nsP2 on viral RNA synthesis and infectivity. CHIKV mutants harboring shortened linkers fail to produce infectious virus particles despite showing only relatively mild defects in genomic and subgenomic RNA synthesis. Mutations increasing the length of the interdomain linker have only mild and generally beneficial impacts on virus replication. Thus, our findings link interdomain flexibility with the regulation of viral RNA replication and infectivity of the viral genome.